2021
DOI: 10.3389/fphys.2021.675778
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise During Advance Stage of Uncontrolled Arterial Hypertension

Abstract: AimTo evaluate the influence of physical training on myocardial function, oxidative stress, energy metabolism, and MAPKs and NF-κB signaling pathways in spontaneously hypertensive rats (SHR), at advanced stage of arterial hypertension, which precedes heart failure development.MethodsWe studied four experimental groups: normotensive Wistar rats (W, n = 27), trained W (W-EX, n = 31), SHR (n = 27), and exercised SHR (SHR-EX, n = 32). At 13 months old, the exercise groups underwent treadmill exercise 5 days a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…NOX activity may be enhanced by several stimuli, such as cyclic stretch, angiotensin II, α-adrenergic agonists, endothelin-1, and TNF-α, many of which are relevant to left ventricular hypertrophy and heart failure [ 98 ]. Studies have shown both increased and unchanged myocardial and skeletal muscle NOX activity during cardiac injury [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Differences in experimental models and cardiac injury levels could be involved in the divergent results.…”
Section: Oxidative Stress and Agingmentioning
confidence: 99%
“…NOX activity may be enhanced by several stimuli, such as cyclic stretch, angiotensin II, α-adrenergic agonists, endothelin-1, and TNF-α, many of which are relevant to left ventricular hypertrophy and heart failure [ 98 ]. Studies have shown both increased and unchanged myocardial and skeletal muscle NOX activity during cardiac injury [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Differences in experimental models and cardiac injury levels could be involved in the divergent results.…”
Section: Oxidative Stress and Agingmentioning
confidence: 99%
“…They also reported that the amount of phosphorylated ERK1/2 increased significantly by 134.3%, 137.1%, and 237.1% when the rats ran at low, medium, and high intensity running, respectively, for four weeks (17). In another study, and despite the fact that ERK1/2 phosphorylation was initially eliminated after stimulation of excess pressure, it did not reduce the hypertrophic response to exercise-induced overload stimulation (13). Exercise has been documented to activate several MAPK pathways in the heart, an effect that gradually diminishes with the development of exerciseinduced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 95%
“…It is generally accepted that ERK1/2 activation is essential for cardiac hypertrophy (29). However, several partially contradictory studies have determined that ERK1/2 may not only lead to maladaptive cardiac hypertrophy but also to physiological hypertrophy (30,31) or that it may have no effect on cardiac hypertrophy (13). In addition, Lu et al showed that the ERK1/2 signaling pathway uniquely regulated the balance between eccentric and concentric growth of the heart (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations